The Folly of Deception: Proverbs 26:24–28, Falsification of Results, and the National University Commission in Nigeria - Uroko, Favour C. (2023)
This study is a theological reflection on Proverbs 26:24–28 and its relevance to the National Universities Commission’s accreditation exercises in Nigerian universities. Existing literature has not adequately looked into the corruption going on between the nuc and universities in Nigeria. In this study, we extended the literature in this area. The nuc usually earmarks periods to visit universities to appraise their infrastructure and manpower capacity. The aim was to ensure that funding for Nigerian universities was judiciously used. Unfortunately, when nuc officials visit universities, they are bribed into writing down in their reports the pass mark for departments and units that are not qualified to have a pass mark. Also, lectures and departmental heads go as far as borrowing classrooms and offices and putting up tags just to escape the accreditation process. This has greatly added to the sorry state of Nigerian universities. A literary analysis was employed. Recommendations were proffered.
Keywords: lecturers; Social Justice; Education; Universities; Proverbs 26; Corruption